Holocene sea-level variability from Chesapeake Bay Tidal Marshes, USA. (November 2019) - Cronin, Thomas M; Clevenger, Megan K; Tibert, Neil E; Prescott, Tammy; Toomey, Michael; Hubeny, J Bradford; Abbott, Mark B; Seidenstein, Julia; Whitworth, Hannah; Fisher, Sam; Wondolowski, Nick; Ruefer, Anna
We reconstructed the last 10, 000 years of Holocene relative sea-level rise (RSLR) from sediment core records near Chesapeake Bay, eastern United States, including new marsh records from the Potomac and Rappahannock Rivers, Virginia. Results show mean RSLR rates of 2.6 mm yr −1 from 10 to 8 kilo-annum (ka) due to combined final ice-sheet melting during deglaciation and glacio-isostatic adjustment (GIA subsidence). Mean RSLR rates from 6 ka to present were 1.4 mm yr −1 due mainly to GIA, consistent with other East Coast marsh records and geophysical models. However, a progressively slower mean rate (<1.0 mm yr −1 ) characterized the last 1000 years when a multi-century-long period of tidal marsh development occurred during the 'Medieval Climate Anomaly' (MCA) and 'Little Ice Age' (LIA) in the Chesapeake Bay region and other East Coast marshes. This decrease was most likely due to climatic and glaciological processes and, correcting for GIA, represents a fall in global mean sea level (GMSL) near the end of Holocene Neoglacial cooling. These pre-historical climate- and GIA-driven Chesapeake Bay sea-level changes contrast sharply with those based on Chesapeake Bay tide-gauge rates (3.1–4.5 mm yr −1 ) (back to 1903). After subtracting the GIA subsidence component, these rates can be attributed to long-term (millennial) global factors of accelerated ocean thermal expansion ( 1.0 mm yr −1 ) and mass loss from alpine glaciers and Greenland and Antarctic Ice Sheets (1.5–2.0 mm yr −1 ).